Difficulty in Emotion Regulation, Metacognition, Psychiatric Symptoms, and Suicide Probability in Obsessive-Compulsive Disorder - Ali İnaltekin; İbrahim Yağcı (AVES YAYINCILIK A.Ş., 2024)
Although an association has been newly reported between obsessive-compulsive disorder (OCD) and an increased risk of suicide, there are only a limited number of studies investigating suicide-related factors in OCD patients. The aim of this study is to evaluate the relationship between dysfunctional metacognitive activity, difficulty in emotion regulation, anxiety, depression, somatization symptom severity, and suicide probability in OCD patients by comparing them with a control group.Difficulties in Emotion Regulation Scale, Metacognition Scale, Suicide Probability Scale, and Patient Health Questionnaire Somatic, Anxiety, and Depression Symptom Scale were administered to 70 OCD patients and 70 healthy controls. The Dimensional Obsession Compulsion Scale was administered to assess OCD symptom dimensions among OCD patients.Dysfunctional metacognition, difficulty in emotion regulation, probability of suicide, depression, anxiety, and somatization symptoms were significantly higher in OCD patients compared to the control group (P < .05). Suicide probability was found to be positively correlated with depression, difficulty in emotion regulation, impulsivity dimension, metacognition, cognitive confidence dimension, contamination, cleaning, and symmetry scores among OCD symptom dimensions (P < .05).Recognizing the factors that were found to be associated with suicide probability in individuals with OCD may be of great importance in identifying patients at higher suicide risk.
Keywords: Neurosciences. Biological psychiatry. Neuropsychiatry; Original Article; RC321-571